Detention under scrutiny - Wdwards, A (Refugee Studies Centre, University of Oxford, 2013)
Seeking asylum is not an unlawful act, yet asylum seekers and refugees are increasingly detained and interned around the world, suffering not only deprivation of liberty but other abuses of their human rights as well. UNHCR’s new detention guidelines challenge governments to rethink their detention policies and to consider alternatives to detention in all cases.